Reflective practices in micro teaching from the perspective of preservice teachers: teacher feedback, peer feedback and self-reflection. Issue 6 (2nd November 2021) - Erdemir, Nihan; Yeşilçınar, Sabahattin
ABSTRACT: Teacher feedback has been often appreciated over the years; however, the current paradigms in teacher education have introduced further reflective practices such as peer feedback and self-reflection. For this purpose, this study aims to explore what reflective practices among teacher feedback, peer feedback and self-reflection could help preservice teachers (PSTs) improve their practice skills in classroom. The study lasted 13 weeks and was conducted with 48 PSTs. Comparison of the usefulness of these reflective practices revealed that teacher feedback and self-reflection were considered useful, respectively. On the other hand, peer feedback was criticized for its undetailed, inefficient and subjective nature. Despite the criticism for peer feedback, PSTs highlighted the importance of using three reflective practices. In consideration of PSTs' negative comments on peer feedback, this study, therefore, suggests that the classroom context should be improved by allocating increased time on peer feedback instruction alleviating anxiety and social barriers among PSTs, and raising peer awareness about the value of their reflective returns. To conclude, the study is expected to provide insights to teacher trainers how to model reflective practices in micro teaching in accordance with sociocultural approach to teacher education.